Produktivitas dan Efisiensi Usahatani Kopi Arabika di Kecamatan Dolok Pardamean Kabupaten Simalungun - Silvia Loren Sidauruk; Mitra Musika Lubis; Siti Sabrina Salqaura; Fastabiqul Khairad (Mahesa Research Institute, 2023)
This study aims to determine the factors that affect the productivity of Arabica coffee farming and to find out how the level of efficiency of Arabica coffee farming prices is in Dolok Pardamean District, Kabupaten Dolok Pardamean. Simalungun. This research is a quantitative descriptive study. This study uses questionnaire data taken directly from Arabica coffee farmers in Dolok Pardamean District, Simalungun Regency. The sample in this study amounted to 33 samples, using purposive sampling technique and taken proportionally. The analytical method used is Multiple Linear Regression analysis. Based on the results of research on factors that influence productivity and efficiency levels of Arabica coffee farming prices, the authors can conclude that: (1) Factors that affect Arabica coffee farming productivity in Dolok Pardamean District are seed variables (X2) and pesticide variables (X4) had a partial effect on the productivity of Arabica coffee farming, while the labor variable (X1) and fertilizer variable (X3) had no partial effect on the productivity of Arabica coffee farming. (2) The level of price efficiency for each factor of production is 17.96. The results of this calculation indicate that the use of labor productivity factors, seeds, fertilizers and pesticides has not been efficient in terms of optimizing factor input prices.